Work flexibility and employee performance through job satisfaction in digital companies - Raden Roro Lia Chairina; Ade Suhara; Dodi Arif; Soni Wirawan; Syech Idrus (Indonesian Indovisi Institute, 2026)
The rapid growth of digital companies has accelerated the adoption of flexible work arrangements, creating new opportunities and challenges for employee performance. This study aims to examine the relationship between work flexibility and employee performance through the mediating role of job satisfaction in digital companies. The research employs a library research approach by reviewing relevant books, peer-reviewed journal articles, research reports, and other scientific publications. Data were collected through systematic literature review and analyzed using content analysis to identify patterns, theoretical relationships, and empirical findings. The results indicate that work flexibility positively influences employee performance when employees experience higher levels of job satisfaction. Flexible work arrangements enhance autonomy, work-life balance, and organizational support, leading to greater motivation, commitment, and productivity. Furthermore, job satisfaction serves as a crucial mediating mechanism that explains how flexible work practices contribute to improved employee performance. These findings provide theoretical contributions to human resource management literature and practical implications for digital companies in designing effective flexible work policies that simultaneously improve employee well-being and organizational performance.